2013
DOI: 10.1080/02607476.2013.765190
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating problem-based learning in teacher education: getting the challenge right

Abstract: The problem-based learning (PBL) literature presents the shift from teacherdirected transmission models of instruction to facilitation as a challenge for PBL tutors. This article reports an in-depth thematic analysis of reflective written responses on PBL of 63 teacher education students enrolled at an Australian university. Attitudes, skills and knowledge represent three distinctive dimensions of facilitation identified by students. Both content and pedagogical knowledge emerged as features of effective facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Useful categories for teacher characteristics for effective PBL implementation include skills, attitudes, and knowledge (Pourshafie & Murray-Harvey, 2013). After preservice teachers experienced PBL as learners, they found that they recognized the need for a shift in attitude about the role of the teacher and that the shifting attitude would influence both knowledge and skills of PBL.…”
Section: Teacher Understanding Of Pblmentioning
confidence: 99%
See 1 more Smart Citation
“…Useful categories for teacher characteristics for effective PBL implementation include skills, attitudes, and knowledge (Pourshafie & Murray-Harvey, 2013). After preservice teachers experienced PBL as learners, they found that they recognized the need for a shift in attitude about the role of the teacher and that the shifting attitude would influence both knowledge and skills of PBL.…”
Section: Teacher Understanding Of Pblmentioning
confidence: 99%
“…The process of being able to hold back teacher input is important for creating a space for student learning. The preservice teachers' statements about knowledge indicated a range of areas where they could see the importance of knowledge for PBL implementation, such as knowing (a) the curriculum and (b) what students know (Pourshafie & Murray-Harvey, 2013).…”
Section: Teacher Understanding Of Pblmentioning
confidence: 99%
“…Expert power is the ability to provide another with the required information, knowledge or expert advice that comes from experience or education (Coon and Mitterer 2008;Nazarko 2004;Phillips and Gully 2011). It is synonymous with the well-known educational concept of ''content knowledge'', which is the knowledge that expert teachers call upon (Pourshafie and Murray-Harvey 2013). Whilst lecturers have expert power because of the knowledge that they have, students gain expert knowledge through both their teachers and the online learning resources they access outside of the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Problem-based instruction poses special challenges in terms of how to best prepare teachers to enact the ideals of reform (De Simone 2008;Ertmer and Simons 2006;Pourshafie and Murray-Harvey 2013). One implication of this study for teacher education is that discussions about launching a problem should include analyses of the implicit assumptions that underlie the PSTs' and ISTs' perspectives.…”
Section: Resultsmentioning
confidence: 97%